A multispecies TAC approach to achieving long-term sustainability in multispecies mixed fisheries. (24th December 2021) - Wo, Jia; Zhang, Chongliang; Ji, Yupeng; Xu, Binduo; Xue, Ying; Ren, Yiping
Abstract: The management of mixed fisheries is complicated by the biological and technical interactions among fish species. We tested a multispecies total allowable catch approach to managing mixed fisheries while accounting for the interactions and changes within fish community. A multispecies size–spectrum model was developed to simulate the dynamic of fish community in North Yellow Sea, China. Three scenarios were evaluated: (1) business-as-usual (BAU); (2) Single-species TAC (SSTAC); and (3) Multispecies TAC (MSTAC, assigning an aggregated total TAC to a selected group of species). Our results showed that BAU reduced biomass of target species to a substantially low level, SSTAC led to loss of fishing opportunity by involving "choke species" with discard ban, while MSTAC had a potential for maintaining long-term yields and community structure. We demonstrated the ecological effects of varying levels of MSTACs on the target and non-target species. Species' responses to MSTAC were stronger when the species had similar feeding and habitat traits to the target species, implying intense competition. Particularly, a 20% decrease in MSTAC could cause an average 17% decline in the biomass of other species through biological interactions in the long-term. MSTAC could be a promising approach to achieving long-term sustainability in data deficient fisheries.